Academic Planning Unit of Public Universities in Nigeria: Challenges and Way Forward - Ahmed Abubakar (International Journal on Integrated Education, 2022)
Planning is very important in university administration. Planning is critical to the attainment of universities goals and objectives. It laid down the foundation for every other process to take off. Academic planning unit in public universities are faced with a lot of challenges. This paper is aimed to discuss the challenges facing Academic planning unit in public Universities in Nigeria. The data were collected from both print and online publications. The paper concluded that inadequate funding, inadequate infrastructural facilities, poor capacity development programme, lack of cooperation, inadequate working materials, poor motivation and shortage of ICT facilities are the major challenges militating against service delivery of Academic planning unit of public Universities in Nigeria. Based on the identified challenges, the paper among other points recommended that the Universities administrators should allocate adequate funds to the Academic planning units and provide efficient and effective ICT facilities among other basic needs as identified in the paper.